Evaluation of the Domino Effect Caused by Pool Fires in a Tank Farm - Shaluf, Ibrahim; Krir, Nuha; Sakal, Salem (Journal of Pure & Applied Sciences, 2024)
Major hazard installations (MHIs), such as oil refineries, petrochemical plants, and terminals, use large-capacity storage tanks for storing crude oil and by-products. Pool fire is one of the most common types of storage tank fire incidents. This technical article aims to investigate the domino effect resulting from a pool fire in a tank farm consisting of eight large floating-roof storage tanks, with a focus on four specific tanks. A crude oil storage tank was selected as the primary tank (source tank). Point source and plume solid models were used to estimate the thermal radiation. It has been noted that the thermal radiation from the source tank to the adjacent tank in the same dike exceeds the threshold heat radiation level and might result in a domino effect; however, the thermal radiation from the source tank alone does not reach the threshold level for the tanks in the other dike. Additionally, it was found that the thermal radiation from both the primary and secondary tanks just reaches the threshold level for the farther-away tank in the other dike. The domino effect occurs provided that the firefighting system is not activated and the emergency response team does not intervene within ten minutes.